Peran Sosial Media Instagram Dalam Pengembangan Strategi Pemasaran Jasa Pada UMKM Pemancingan Kelapa Gading Rembang - Nastasya Uyun Siti Azzahra; Maharani Ikaningtyas (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Social media makes changes to the business world, especially in terms of marketing or promotion. Social media is now a big opportunity for business because they use social media as a source of information delivery. Instagram is one of the social media that provides a place for business people to sell and market their products or services. Instagram is now widely used by the wider community. Anyone can use Instagram happily because the features provided are easy to apply. Instagram social media is used by business people as a means of introducing products or services to buying and selling online. The object of this study is how important is the role of Instagram social media for Kelapa Gading Fishing Services SMEs in Rembang, Blitar, East Java. This research uses qualitative methods, it can be concluded that Instagram plays a very important role for business people to introduce their products or services to people in various parts of the world by utilizing features and posting informative creative content so that readers can easily understand the content of the Instagram social media content.